One-Dimensional Consolidation of Kelang Clay - Taha, Mohd Raihan; Ahmed, Jimjali; Asmirza, Sofian (Universiti Putra Malaysia Press, 2000)
A study on the consolidation behaviour of Kelang clay is presented in this paper. The soil samples taken near the Port of Kelang showed that the clay can be divided into upper marine and the lower river clays. The initial distinction was based on the existence of sea shells in the upper deposits and none in the lower deposits. It has been shown that these two clays have different consolidation properties as well as other basic geotechnical characteristics. Consolidation history indicated that Kelang clay is normally consolidated and may be classified as a high compressibility clay. The overburden pressure due to fill must be neglected in order to obtain the true over consolidation ratio. It was also found that the correlation given by Terzaghi and Peck (1967) provided the best estimates for the compression index, particularly that of the marine clay.